Sequential saccharification and simulationeous fermentation of pineapple waste for bioethanol production - Nur Hidayah, Hussin (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Bioethanol is a renewable source of energy that can be used as an alternative to overcome the depletion of fuel for transportation. It is also friendly to the environment as the burning of bioethanol emits zero net carbon output to the atmosphere. In this study, pineapple wastes were used to produce bioethanol via Sequential Saccharification and Simultaneous Fermentation (SSSF) a modified version of Simultaneous Saccharification and Fermentation (SSF) by using cellulase and Saccharomyces cerevisiae. SSSF was performed on the pineapple waste at 5.0% (w/v) substrate load, with and without the presence of cellulase, for five days under anaerobic conditions to compare the bioethanol yield. Phenol-Sulphuric Total Carbohydrate assay and High Performance Liquid Chromatography (HPLC) were used to analyze the samples taken from fermentation broth. Based on the results, SSSF of 5% (w/v) treated pineapple waste gives higher ethanol yield compared to SSSF of 5% (w/v) untreated pineapple wastes which are 5.85 g/l and 2.54 g/l respectively at 120 hour of fermentation. This study has proven that SSSF of pineapple waste was able to liberate bioethanol and it can be considered to be used as a substrate for industrial scale bioethanol production in future.